Livestock's role in boosting nutrition in Africa - Dube, Sikhalazo (Farming First, 2017)
In a region where malnutrition and stunting levels are high, animal-source foods can boost protein levels for children who need it. Sikhalazo Dube explains why livestock is critical for boosting nutrition in Africa.